Effects of Sowing Dates and Weed Management on Weed Growth and Nutrients Depletion by Weeds and Uptake by Wheat (Triticum Aestivum L.) Under Shiwalik Foothills Plains of Jammu - Sharma, Neetu; Kumar, Anil; Sharma, BC; Kumar, Rakesh; Verma, Akhil; Kumar, Manish (Bangladesh Journal of Botany, 2021)
A field experiment was conducted to study the effect of sowing dates and weed management practices on weed growth and nutrients depletion by weeds and uptake by wheat. The results revealed that crop sown on 15th November significantly reduced the weed density and its dry matter was compared to crop sown on 25th December. Among weed management treatments, ready mix application of sulfosulfuron + metsulfuron at 30 g/ha + 2 g/ha followed by metribuzin (210 g/ha) showed significantly lowest density and dry weight of weeds. Wheat crop sown on 15th November showed significantly lowest nutrient depletion by weeds and highest yield, nutrients uptake by wheat crop. Significantly lowest nutrient depletion by weeds, highest growth parameters, yield attributes, yield and nutrient uptake by wheat crop were recorded with the ready mix application of sulfosulfuron + metsulfuron at 30 g/ha + 2 g/ha. Regression equation revealed that unit increase in the weed control efficiency increased the grain yield by 25.56 kg/ha. Bangladesh J. Bot. 50(2): 311-318, 2021 (June)